Comparison of the effect of EMLA ointment and lidocaine spray, along with the use of rhythmic breathing on the intensity of pain caused by the insertion of needles in the arteriovenous fistula among hemodialysis patients: A clinical trial - Mohammad Gholizadeh; Javad Bazeli; Fatemeh Javaherforooshzadeh; Mohammad Vaseie; Maryam Moradi; Ali Mohammadpour (حیات, 2023)
Background & Aim: Patients undergoing hemodialysis commonly experience discomfort due to the insertion of needles into their arteriovenous fistula. The aim of the study was to compare the effect of EMLA ointment and lidocaine spray, along with the use of rhythmic breathing on the intensity of pain caused by the insertion of needles in the arteriovenous fistula among hemodialysis patients. Methods & Materials: This study was a randomized clinical trial conducted on a total of 80 patients who were referred to Imam Khomeini and Golestan hospitals in Ahvaz in 2022. The numerical pain measurement scale was used as the data collection tool. The participants were selected using the convenience sampling method and then randomly allocated into two groups. In the EMLA ointment group (n=39), a total of 2 grams of EMLA ointment was applied to the target area 60 minutes before the hemodialysis procedure. In the lidocaine spray group with rhythmic breathing (n=41), 2 puffs of lidocaine spray were administered along with rhythmic breathing 5 minutes prior to needle insertion. The pain intensity was then measured and recorded. The collected data was analyzed using descriptive and inferential statistics in SPSS version 20, with a significance level set at 0.05. Results: The group receiving EMLA ointment and the group receiving lidocaine spray, with rhythmic breathing had mean pain scores of 1.95±1.09 and 2.12±1.10, respectively. Although the mean pain score in the EMLA ointment group was lower than that in the lidocaine spray group with rhythmic breathing, the difference was not statistically significant (P=0.479). Conclusion: The findings of this study indicate that both EMLA ointment and lidocaine spray, along with the use of rhythmic breathing, have comparable efficacy in reducing pain among hemodialysis patients. Therefore, considering the patient's condition, the utilization of either of these methods is recommended. Clinical trial registry: IRCT20220512054826N1